2021
DOI: 10.1371/journal.pone.0257247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced periodontal self-care in patients with early-stage periodontal diseases on endothelial function: An open-label, randomized controlled trial

Abstract: Although a significant association between periodontal disease and atherosclerotic cardiovascular disease has been reported, their cause-to-effect relationship remains controversial. This randomized controlled clinical trial aimed to investigate the effect of advanced self-care on atherosclerotic cardiovascular disease-related vascular function markers flow-mediated brachial artery dilatation (FMD) and serum asymmetric dimethylarginine (ADMA) level in patients with early-stage periodontal disease. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…These findings are consistent with data reported by Seinost et al [ 37 ], who showed that flow-mediated dilation was significantly lower in patients with periodontitis when compared with healthy control (6.1% ± 4.4% vs. 8.5% ± 3.4%, p = 0.002), and that periodontal treatment caused a significant improvement in FMD (9.8% ± 5.7%; p = 0.003 in comparison to baseline values) and a simultaneously significant decrease in C-reactive protein concentrations ( p = 0.026). To date, limited studies have examined ADMA concentrations in relation to periodontitis and endothelial function [ 29 ]. Recently, ADMA was proposed to be useful for CV risk stratification and for predicting endothelial function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with data reported by Seinost et al [ 37 ], who showed that flow-mediated dilation was significantly lower in patients with periodontitis when compared with healthy control (6.1% ± 4.4% vs. 8.5% ± 3.4%, p = 0.002), and that periodontal treatment caused a significant improvement in FMD (9.8% ± 5.7%; p = 0.003 in comparison to baseline values) and a simultaneously significant decrease in C-reactive protein concentrations ( p = 0.026). To date, limited studies have examined ADMA concentrations in relation to periodontitis and endothelial function [ 29 ]. Recently, ADMA was proposed to be useful for CV risk stratification and for predicting endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Tsioufis et al [ 38 ] conducted a trial involving untreated hypertensive subjects with concomitant periodontal disease and demonstrated the reduction of asymmetric dimethylarginine (ADMA) concentration after periodontal treatment. Okada et al [ 29 ] recently investigated the impact of periodontal treatment on ADMA levels and FMD values. In contrast with our observations, the authors reported no significant between-group differences in FMD (mean difference, −0.2%; 95% CI, −1.4–0.9; p = 0.708) and serum ADMA levels (mean difference, 0.01 nmol/L; 95% CI, −0.00–0.03; p = 0.122).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of improvement was associated with improvement in measures of periodontal disease ( 17 ). More recent studies did not find clinical evidence for a positive effect on endothelial function after periodontal therapy, and therefore a possible cause-to-effect relationship remains controversial ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%